Autistic Adult Knowledge of the Americans with Disabilities Act and Employment-Related Rights - David Schena; Rocio Rosales (MDPI AG, 2023)
As the autism community continues to grow, it is increasingly important to evaluate strategies to teach workplace-related skills to the members of this community. One of these skills is self-advocacy, defined by Test et al. as consisting of four components: self-knowledge, knowledge of rights, communication, and leadership. This study aimed to address the second component of this definition, knowledge of rights. Three autistic adults learned information about key terms from the Americans with Disabilities Act. Participants practiced identifying legal rights related to discrimination and inability to provide certain accommodations in a series of short text scenarios, using instructor-modeled rehearsal of similar scenarios as the independent variable. Results show that each participant entered the study with an existing level of knowledge and ability to interpret the rights of various scenarios (30-60% correct during baseline) and that training resulted in small improvements (a 20-40% increase) in accurate scenario interpretation. Future research should include additional techniques, such as role play, to enhance performance accuracy and examine long-term retention and generalization of the skills acquired. Social validity feedback suggests that the training used in this study was acceptable to participants and may be amenable to future studies.